2023
DOI: 10.1038/s41551-023-01062-w
|View full text |Cite
|
Sign up to set email alerts
|

Posterior scleral birefringence measured by triple-input polarization-sensitive imaging as a biomarker of myopia progression

Abstract: In myopic eyes, pathological remodelling of collagen in the posterior sclera has mostly been observed ex vivo. Here we report the development of triple-input polarization-sensitive optical coherence tomography (OCT) for measuring posterior scleral birefringence. In guinea pigs and humans, the technique offers superior imaging sensitivities and accuracies than dual-input polarization-sensitive OCT. In 8-week-long studies with young guinea pigs, scleral birefringence was positively correlated with spherical equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…To our knowledge, this is the first study that determined the orientation and density of the scleral collagen fibers in a wide area of the posterior fundus. Previous studies using PS-OCT in human participants primarily focused on a restricted region around the optic disc and, in some cases, extended their observations to the macular area but no further. Willemse et al examined the architecture of the peripapillary sclera using PS-OCT, and they found radially oriented scleral collagen fibers over a circumferentially arranged layer around the optic disc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first study that determined the orientation and density of the scleral collagen fibers in a wide area of the posterior fundus. Previous studies using PS-OCT in human participants primarily focused on a restricted region around the optic disc and, in some cases, extended their observations to the macular area but no further. Willemse et al examined the architecture of the peripapillary sclera using PS-OCT, and they found radially oriented scleral collagen fibers over a circumferentially arranged layer around the optic disc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the magnitude of the birefringence that reflects the density of fibers, PS-OCT can also show the axis of orientation or the optic axis of the birefringence that is related to the orientation of the fiber bundles. Optic axis imaging of the sclera of the fundus has been reported in the eyes of rats, healthy humans, guinea pigs, and normal and highly myopic eyes of humans . However, to our knowledge, there has not been a study focused on a DSM that has specific variations in its morphologic features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge on progression mechanisms will allow us to design individualized treatment combinations improving the cost-effectiveness of known and new myopia control methods. Deep learning methods based on fundus images [ 252 ], as well as new imaging tools [ 253 ], are promising new approaches to delivering applicable methods into clinics. Such strategies will provide tools for assessing and tailoring an individual child’s myopia management.…”
Section: Discussionmentioning
confidence: 99%
“…Polarization is one of the fundamental characteristics of light. Polarization detection plays a critical role in a lot of important areas, including remote sensing, biomedicine, navigation, and quantum communication. With the trend of miniaturization, on-chip polarimeters have attracted a lot of research interest. Usually, the polarization dependences of these devices are fixed immediately after fabrication. The lack of dynamic reconfigurability impedes the development of polarimetry toward intelligence, which would be a salient feature of the next-generation polarimeters.…”
mentioning
confidence: 99%